EXCEPTION CLAUSES IN BOOK CONTRACTS REVIEWED ACCORDING TO CIVIL LAW AND THE CONCEPT OF IJARAH CONTRACTS: A CASE STUDY ON SPARTAN RENTAL CAR JAMBO TAPE BANDA ACEH - Muhammad Jimmi (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2020)
A standard contract is a contract that has been made in a standard form, or printed in large quantities with blanks for several parts that are the object of the transaction, such as the amount of transaction value, type, and amount of goods transacted, so that it does not open opportunities for other parties to negotiate what will be agreed to be stated in the contract. Based on the results of the research that Spartan Rental Car does not use standard clauses, but with so many service providers that a standard contract is made to facilitate rental activities and the standard contract that has been used there are clauses that burden service users and are prohibited by law called exclusion clauses. The current standard contract is used to take advantage of the owner of the capital and give disadvantages to service users. Overcoming the polemics of contract transactions like this, it is hoped that there will be legal rules that can provide fresh air to service users and business capital owners.